2012
DOI: 10.1108/01409171211276918
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating the acquisition of strategic skills

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:403714 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 68 publications
0
14
0
2
Order By: Relevance
“…Previously, it was believed that the employee's effective work is provided by this category. Nevertheless, in the last decade more and more attention has been paid to soft skills, that is, the ability to work in a team and argue to defend one's point of view and resolve conflicts (Parente et al, 2012). The personnel training system should simultaneously develop both categories of skills in students; this approach is reflected in a combination of different methods of conducting classes.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was believed that the employee's effective work is provided by this category. Nevertheless, in the last decade more and more attention has been paid to soft skills, that is, the ability to work in a team and argue to defend one's point of view and resolve conflicts (Parente et al, 2012). The personnel training system should simultaneously develop both categories of skills in students; this approach is reflected in a combination of different methods of conducting classes.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, they can focus on designing courses related to leadership, team work and strategic thinking competencies, as top priority for investment in upper level of management. However, most competencies in this cluster are not cognitive in nature; hence, selecting such learning methods as experience-based in a group/team environment could be consider to ensure the achievement of learning outcomes (Parente et al. , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The same applies to relief aid organisations, whose competent staff are able to institute and implement accountability mechanisms aimed at satisfying both the donor and the beneficiary. Meanwhile a study by Parente, Stephan, & Brown, (2012), established that managerial competencies lead to accountability. Additionally, Bakalikwira et al, (2017) in their study conducted in the health sector in Uganda found a positive and significant relationship between managerial competencies and accountability.…”
Section: Managerial Competencies and Accountabilitymentioning
confidence: 99%